3y-x=6 on a graph will be a line.
Substitute 0 for x then solve for Y. 3y-0=6, 3y = 6, y = 6/3 = 2.
So your first point (y intercept) is (0,2).
Next substitute 0 for y then sove for x. 3(0)-x=6, 0 - x = 6, x = 6(-1) = -6
So point #2 (x intercept) is (-6, 0).
Plot the two points and draw a line.
the graph is moved down 6 units
It is 6 and the y intercept is -1
-2/3
The starting point on the y-axis changes from -2 to 6.
4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)
8
y=6
the graph is moved down 6 units
The graph is a circle with a radius of 6, centered at the origin.
2x=3yx=3y-32(3y-3)=3y substitution6y-6=3y distributive property3y=6 addition property of equalityy=2 multiplication(division) property of equalityx=3(2)-3 substitutionx=6-3x=3
Graph and Table: http://i50.tinypic.com/szhr4k.png
It is 6 and the y intercept is -1
The equation 2x - 3y = 6 is a linear equation and a linear equation is always has a straight line as a graph
8
-4
+ 1/8
-2/3